Estudo da produção de enzimas amilolíticas utilizando resíduo agroindustrial (Manipueira) - Oliveira, Thaynah Silveira de (2017)
Amylolytic enzymes are considered of great biotechnological importance. The search for amylase excretory microorganisms is considered a continuous process since there is a great demand in the industries and a need for more specific enzymes for each process. An economically viable alternative for the production of these enzymes is the use of starch-rich residues instead of high-cost synthetic culture media. Among these residues, manipueira is highlight, a liquid residue generated in the pressing stage of the cassava to obtain the flour, highly produced in the state of Sergipe and that presents nutrients necessary for the growth of microorganisms. The present work aimed to isolate microorganisms producing amylolytic enzymes, using manipueira as a source of isolation and means of production through submerged fermentation. A sequence of factorial planning was proposed to find an optimum region of the process conditions, aiming a greater amylolytic production and greater utilization of the residue. The amylase production profile was delineated from the dextrinizing and saccharifying activities. Isolation was carried out through the sowing technique by nutrient and potato dextrose, which showed three strains capable of excreting amylolytic enzymes (TP02, TN03, TN04), with emphasis on the enzymatic activity index of TN04 isolate of 9.28. The TP02 strain was selected as the most important activity (16.15 U.mL-1 dextrinizing and 0.66 U.mL-1 saccharifying) by fermentation in synthetic liquid with 1% starch medium as an inducer, being thus employed in the study of the production of amylases using the manipueira crude and treated as substrate, to investigate the influence of the manipueira treatment. The activity values when using the manipueira in its treated and crude form were, respectively, for dextrinizing activity (34.78 U.mL1 and 36.03 U.mL-1 ), and for saccharifying activity (37.52 U. mL -1 and 36.81 U.mL-1 ). These values were higher than when using synthetic medium, confirming the potential of this residue in the production of amylases. The treatment of the manipueira did not result in a great difference in the production of the amylase, with that the crude manipueira was used in the planning aiming at the decrease of the costs of the production By means of the fractional factorial design 2 (4-1) it was possible to select the variables with the greatest significant effects (p <0.05) for the production of amylases, which were pH and manipueira concentration, and set temperature values at 30 ° C and stirring at 100 rpm, by analyzing the behavior of the means between these factors. The complete factorial design 32 made it possible to find an optimal region for the process conditions. The optimal range for pH is between 7.5 and 8, and for manipueira concentration, 80% to 100%. The highest values of dextrinizing and saccharifying activity in the assay with pH 8 and 100% of manipueira concentration, evaluated at 144 hours were 97.39 U.mL-1 and 79.86 U.mL-1 , respectively. The enzymatic extract produced under optimum region conditions has the optimum temperature for hydrolysis at 50 to 70 °C and optimum pH 7. These data demonstrate the potential of the isolated microorganism and the use of the manipueira to obtain amylolytic enzymes with promising aplications in a wide range of industries.